Anaplastic large‐cell lymphoma associated with breast implants: A unique entity within the spectrum of peri‐implant effusions. Issue 11 (31st March 2014) - Chai, Siaw Ming; Kavangh, Simon; Ooi, Sin Sin; Sterrett, Gregory F.; Cull, Gavin; Plunkett, Myfanwy; Spagnolo, Dominic; Amanuel, Benhur; Joske, David; Leslie, Connull; Barham, Tony; Frost, Felicity
<x xml:space="preserve">Abstract</x> Anaplastic large‐cell lymphoma (ALCL) is a rare and newly described complication associated with breast implants. Patients often present with a peri‐implant effusion, which is amenable to fine‐needle aspiration. The laboratory handling of peri‐implant effusions for cytology and ancillary studies is as crucial as recognizing the characteristic cytology of ALCL. All cases of peri‐implant effusions were retrieved from the PathWest database between January 2003 and May 2013, yielding four cases of breast implant‐associated ALCL and six benign samples. The cytological features were evaluated and information from ancillary studies collated. Clinical and follow‐up histology was available in all cases. All ALCL cases contained highly atypical lymphoid cells including 'hallmark' cells. In contrast, benign peri‐implant effusions showed a mixture of inflammatory cells, being either neutrophil‐rich (three cases) or lymphocyte‐rich (three cases). A CD30 positive, ALK1 negative immunophenotype was demonstrated in all cases on cell block immunohistochemistry. Flow cytometry and T‐cell receptor clonality studies confirmed aberrant T‐cell immunophenotype in four of four and clonally rearranged T‐cell receptor antigens in three of three cases. ALCL was identified in three of four subsequent capsulectomies. Staging confirmed disease limited to the capsular tissue or peri‐implant effusion in all cases. None of the six patients with benign peri‐implant effusions developed lymphoma during follow‐up. Cases of ALCL accounted for 40% of peri‐implant effusions received over a 10‐year period, indicating the rarity of these samples and the high likelihood of malignancy. Awareness of this entity and its presentation should allow for appropriate triage of these specimens and definitive diagnosis on effusion specimens. Diagn. Cytopathol. 2014;42:929–938. © 2014 Wiley Periodicals, Inc.